FcɛR1γ-based activating chimeric antigen receptor enhanced natural killer cell function against HLA-E+ cells - Lanier, Lewis; Greenland, John R; Momburg, Frank; Calabrese, Daniel R; Shemesh, Avishai (The journal of immunology, 2025)
FcɛR1γ is a transmembrane adaptor protein that regulates the activating receptors NKp30, NKp46, and CD16 expression and function in human natural killer (NK) cells. HLA-E expression by cancer cells suppresses NK cell function through interaction with NKG2A. Here, we engineered human NK cells to express a modified FcɛR1γ with a 4-1BB co-stimulatory motif. FcɛR1γ41BB expression led to the upregulation of NKp30, NKp46, and CD16 expression and enhanced NKp30- and CD16-mediated target cell lysis. Against cells expressing HLA-E, FcɛR1γ41BB improved NK cell lytic function relative to FcɛR1γ. We then generated an CD19ScFv-CD8hinge-FcεR1γ41BB(TM-IC) CAR (FCRG10). Engineering human NK cells to express FCRG10 led to upregulation of NKp30 and CD16, and improved NK cell-mediated cytotoxicity against cells co-expressing B7H6, CD19, and HLA-E relative to NK cells expressing the conventional CD19CAR41BB-CD3ζ with a CD8 transmembrane domain. Our results indicate that modification of FcɛR1γ enhances NK cell lytic function mediated by several activating receptors and improves CAR NK cell response in conditions favoring NK cell suppression by HLA-E. Our work may contribute to NK cell-based cancer immunotherapy mediated by co-recognition of stress-induced ligands, antibody-coated cells, and tumor-associated antigens.